Effect of the Nucleosome-Depleted Region in the Transcribed Regions of Saccharomyces cerevisiae Genes on Exogenous Gene Expression - Shuyan Wang; Hong Li; Xiaolong Li (Applied Sciences)
Nucleosome sequence composition is closely associated with gene expression. The nucleosome-depleted region (NDR) within the transcriptional regulatory region of S. cerevisiae genes plays a crucial role in the regulation of gene expression. To investigate the effect of NDR length on transgene expression, we conducted an experiment to regulate exogenous gene expression by manipulating the NDR in the transcriptional regulatory region of S. cerevisiae genes. We selected the ±1 nucleosome and NDR sequences between them of six S. cerevisiae genes as transcriptional regulatory elements to drive GFP gene expression. Our findings revealed that under the regulation of long NDR, both the mRNA and protein expression levels of the GFP gene were significantly increased compared to those under short NDR. Furthermore, reducing the long NDR by 80 bp (NDR−) resulted in a significant reduction in the level of GFP gene expression. However, lengthening the short NDR length by 80 bp (NDR+) significantly increased the expression level of the GFP gene. This is attributed to the fact that longer NDR facilitates transcription factor (TF) binding without energy expenditure, thereby enhancing transcription efficiency. In contrast, shorter NDR necessitates the disassembly or sliding of the −1 nucleosome to accommodate TF binding, which consumes energy and reduces the transcription efficiency. These results demonstrate that the expression system constructed using the ±1 nucleosome and NDR sequences can effectively modulate exogenous gene expression, offering a novel design approach for transgene expression control.